Human herpes virus reactivations and dynamic cytokine profiles in patients with cutaneous adverse drug reactions – a prospective comparative study. Issue 5 (16th March 2015) - Chen, Y.‐C.; Chiang, H.‐H.; Cho, Y.‐T.; Chang, C.‐Y.; Chen, K.‐L.; Yang, C.‐W.; Lee, Y.‐H.; Chu, C.‐Y.
Abstract Background Sequential human herpes virus (HHV) reactivation is well known in drug reaction with eosinophilia and systemic symptom (DRESS), but such a phenomenon has seldom studied in other types of cutaneous adverse drug reactions (cADRs). Moreover, the association between viral reactivations and cytokine or chemokine changes is largely unknown. We aimed to evaluate the viral reactivation rates of HHV‐6, HHV‐7, Epstein–Barr virus (EBV), and cytomegalovirus (CMV) in different cADRs and their impacts on clinical prognosis. Cytokine and chemokine changes with viral reactivations were also examined. Methods A prospective study was conducted to monitor the viral statuses of patients with different cADRs by polymerase chain reaction and serum‐specific antibody titers. Changes in plasma cytokine and chemokine levels were also evaluated by sequential blood samples. Results Among the various cADRs, HHV‐6 reactivation was only observed in DRESS, but EBV and CMV could be detected in other cADRs. Many proinflammatory cytokines and chemokines, including interleukin (IL)‐1β, IL‐2, IL‐6, interferon‐γ, tumor necrosis factor‐α, were significantly lower in DRESS patients with HHV‐6 reactivation when compared to those without HHV‐6 reactivation. In addition, these mediators were significantly lower before and during HHV‐6 reactivation, compared to cytokine levels after HHV‐6 reactivation in the same patient. Conclusion HHV‐6 reactivation was only observed in DRESS patients, not in any other cADR. In DRESS patients, some proinflammatory cytokines were significantly lower before or during HHV‐6 reactivation.